(untitled) (The Pakistan Development Review, 2001)
According to Jones and Marjit (1992), in a two-sector, full-employment model it is not possible to show that growth in the foreign capital employed in the export sector of a small open economy will lead to a fall in the welfare in the presence of a protected import-competing sector. In this short paper, we have shown that one may get the immiserising result even in this framework if the inflow of foreign capital into the export sector is accompanied by technology transfer, which leads to a fall in the labour-output ratio in this sector.